Magical Phenomena in Reality in Rick Riordan’s Percy Jackson and The Olympians: The Lightning Thief - Anik Cahyaning Rahayu; Sudarwati Sudarwati; Susie Chrismalia Garnida (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2024)
This research examines the elements of magical realism, using descriptive qualitative method, a literary genre depicting magic in the modern world, in Rick Riordan's "Percy Jackson and the Olympians: The Lightning Thief." Applying Wendy B. Faris' theory of magical realism's five characteristics: the irreducible element, the phenomenal world, unsettling doubts, merging realism, and disruption of time/space/identity. The research identifies these aspects in the novel. The analysis reveals the novel contains irreducible magical elements like worlds, characters, and objects, exemplified by Percy's encounter with the shape-shifting monster Erinyes disguised as his teacher. The phenomenal world encompasses magical places and beings. Unsettling doubts arise from Percy directly addressing the reader about his experiences. Merging realism intertwines the magical realm rooted in myths with the tangible world, as monsters and gods frequently intermingle with reality. Disruption of time manifests when Percy experiences slowed time at the Lotus Hotel during his quest. The study concludes that "The Lightning Thief" exhibits all five characteristics of magical realism by integrating mythological magic into the contemporary setting. Irreducible magical elements, a phenomenal, magical world, narrator-induced unsettling doubts, the merging of mythical and real realms, and space-time distortions collectively categorize the novel as an exemplar of magical realist fiction.